Epigenetic-mediated tumor suppressor genes as diagnostic or prognostic biomarkers in gastric cancer. (June 2013) - Otani, Koji; Li, Xiaoxing; Arakawa, Tetsuo; Chan, Francis KL; Yu, Jun
Gastric cancer is believed to result in part from the accumulation of multiple genetic and epigenetic alterations leading to oncogene overexpression and tumor suppressor loss. Tumor suppressor genes are inactivated more frequently by promoter methylation than by mutation in gastric cancer. Identification of genes inactivated by promoter methylation is a powerful approach to discover novel tumor suppressor genes. We have previously identified tumor suppressor genes in gastric cancer by genome-wide methylation screening. The biological functions of these genes are related to cell adhesion, ubiquitination, transcription, p53 regulation and diverse signaling pathways. Some of the tumor suppressor genes are of particular clinical importance as they can be used as predictive biomarkers for early diagnosis or ongoing prognosis of gastric cancer.